How reliable is your diagnosis? - Gruber, Achim D.; Wehrend, Axel; Steidl, Thomas; Kramer, Katharina; Merbach, Sabine; Baumgärtner, Wolfgang; Buyle, Thomas; Weisser, Niclas-Frederic; Beineke, Andreas (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2024)
The effectiveness and justification of every therapy and other clinical decisions is based on a correct diagnosis. However, many types of test results can contain uncertainties that may lead to clinically incorrect decisions. The same applies to the reliability of expert opinions for legal disputes. Adequate communication of diagnostic and expert uncertainties in the examination report or expert opinion is therefore crucial for avoiding incorrect decisions. The liability of the person providing the service is also affected. However, uncertain or even erroneous findings can have various causes, only some of which are known to the examining or commissioning person. This article provides an overview of 3 different types of susceptibility to errors using the example of pathological biopsy and cytology examinations, which can also be transferred to other veterinary disciplines in a similar way. A solid understanding of the possible sources of error as well as adequate communication and discussion of case-specific, limited probabilities in investigation reports and expert opinions make a significant contribution to avoiding incorrect decisions. However, commonly used terms such as "highly probable", "suspected" or "cannot be ruled out" are sometimes interpreted in unclear or divergent ways, which are explained here with recommendations for uniform use. This is intended to enable the person making the decision, if necessary, to initiate further diagnostic tests or gather further evidence in the context of all other available data in order to reduce the risk of error as far as possible.
Keywords: Causes of errors; uncertainty; communication; liability; forensics; probability